2013
DOI: 10.1155/2013/289185
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Delirium in the Intensive Care Unit Predicts Worse Outcomes in Liver Transplant Recipients

Abstract: Intraoperative transfusion of packed red blood cells, pretransplantation renal replacement therapy and APACHE II score are predictors for the development of delirium in intensive care unit patients post-OLT and are associated with increased hospital lengths of stay and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
64
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(78 citation statements)
references
References 45 publications
8
64
6
Order By: Relevance
“…Although few studies have examined the impact of delirium on clinical outcomes in transplant recipients, Lescot and colleagues[35] found that delirium following liver transplant was associated with significantly elevated length of hospital duration and mortality, independent of markers of disease severity. However, to our knowledge, no studies have previously demonstrated that delirium is associated with longer hospital duration among lung patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although few studies have examined the impact of delirium on clinical outcomes in transplant recipients, Lescot and colleagues[35] found that delirium following liver transplant was associated with significantly elevated length of hospital duration and mortality, independent of markers of disease severity. However, to our knowledge, no studies have previously demonstrated that delirium is associated with longer hospital duration among lung patients.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, a recent study by Iglesias et al [51] refutes this finding that independent predictors of recovery of kidney function postliver transplant were the absence of hepatic allograft dysfunction, younger donor age and lower recipient alanine aminotransferase at time of liver transplant, whereas the recipient of RRT, even in excess of 8 weeks, did not predict postliver transplant kidney function. Finally, Lescot et al [55] showed that delirium postliver transplant correlated with preliver transplant illness severity and portended a three-fold increase in 1-year mortality. Postliver transplant, cirrhotic patients are at risk of hyponatremia, calcineurin inhibitor-induced neurotoxicity (ECIIN) and delirium.…”
Section: Challenges In the Posttransplant Care Of Critically Ill Cirrmentioning
confidence: 99%
“…As delirium has been associated with worse survival and outcomes in other critically ill 3 and transplant populations 8 , it could be expected to have a similar effect in lung transplant recipients. The available data on delirium after lung transplantation is limited to a few small single center studies 9–11 .…”
Section: Introductionmentioning
confidence: 99%